Correlation between nursing dependence and discharge readiness in middle-aged and elderly patients undergoing coronary artery bypass grafting (中老年冠状动脉旁路移植术后患者护理依赖与出院准备度的相关性研究) - JI Yanxia (纪延霞); ZHENG Donglian (金亚楠); MA Xiaoying (郑栋莲); MA Fuzhen (马晓莹); JIN Yanan (马富珍); GUO Shuping (郭淑萍) (Association of Integrative Nursing, 2023)
Objective To investigate the nursing dependence level and discharge readiness of middle-aged and elderly patients undergoing coronary artery bypass grafting, and to explore the correlation between them. Methods A questionnaire survey by using Readiness for Hospital Discharge Scale(RHDS) and Care Dependency Scale (CDS) was conducted between February 2021 and August 2022 among 130 coronary artery bypass grafting patients who were scheduled to be discharged from hospital. Results The total score of CDS in middle-aged and elderly patients undergoing coronary artery bypass grafting was (54. 86(+-)4. 38), and the total score of RHDS was (169. 64(+-)16. 32). Pearson correlation analysis showed that the score of CDS in middle-aged and elderly patients undergoing coronary artery bypass grafting was positively correlated with the score of RHDS. Conclusion Age and medical payment ratio were the main factors affecting the degree of nursing dependence of patients. Medical staff should focus on the elderly patients and the patients with heavy family medical burden payment ratio. To develop targeted discharge planning services to reduce patients' nursing dependence. (目的 了解中老年冠状动脉旁路移植术患者护理依赖水平和出院准备度现状, 并探讨两者间的相关性。方法 于2021年2月-2022年8月对130例拟计划出院的冠状动脉旁路移植术患者进行问卷调查。结果 中老年冠状动脉旁路移植术患者护理依赖总分为(54. 86(+-)4. 38)分, 出院准备度总分为(169. 64(+-)16. 32)分, Pearson相关分析显示: 中老年冠状动脉旁路移植术患者护理依赖量表(CDS)得分与出院准备度量表(RHDS)得分呈显著正相关关系。结论 年龄和医疗支付比例是患者护理依赖严重程度的独立影响因素, 建议医护人员应重点关注高龄和家庭医疗负担支付比例较重的患者群体, 制定针对性的出院计划服务进而降低患者护理依赖水平。)